MIS-C-Implications for the Pediatric Surgeon: An Algorithm for Differential Diagnostic Considerations - Nora Manz; Claudia Höfele-Behrendt; Julia Bielicki; Hanna Schmid; Matthias S. Matter; Isabella Bielicki; Stefan Holland-Cunz; Stephanie J. Gros (MDPI AG, 2021)
Background: multisystem inflammatory syndrome in children (MIS-C) is a new disease associated with a recent infection with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Affected children can present predominantly with abdominal symptoms, fever and high inflammatory parameters that might lead to a consult by the pediatric surgeon and an indication for surgery. Methods: clinical data of three patients with MIS-C that underwent surgery were collected. Histopathological analysis of the appendix was performed. Results: we present the clinical course of three children with fever, abdominal pain and vomiting for several days. Clinical examination and highly elevated inflammation markers led to indication for laparoscopy; appendectomy was performed in two patients. Because of intraoperative findings or due to lack of postoperative improvement, all patients were reevaluated and tested positive for MIS-C associated laboratory parameters and were subsequently treated with corticosteroids, intravenous immunoglobulins, acetyl salicylic acid and/or light molecular weight heparin. Conclusions: we discuss the implications of MIS-C as a new differential diagnosis and stress the importance of assessing the previous medical history, identifying patterns of symptoms and critically surveilling the clinical course. We implemented an algorithm for pediatric surgeons to consider MIS-C as a differential diagnosis for acute abdomen that can be integrated into the surgical workflow.